Numerical investigation of turbulent flow over a small-scale vertical axis wind turbine - Ahmed Bekhti; Maria Guellal; Hafsa Charf; Ali Boudis; Madjid Tata; Dawoud Hamane; Abdallah Touaibia (Revue des Énergies Renouvelables, 2024)
The present paper aims to analyse the aerodynamics of turbulent fluid flow over a vertical axis wind turbine (VAWT). A 2D study is carried out for a two-bladed SAVONIUS wind turbine, where the rotor diameter is D=20cm. The governing equations (Unsteady Reynolds Averaged Navier Stokes URANS) are solved numerically using a CFD (computational fluid dynamics) open-source code based on the finite volume method; the SST turbulence model is applied for the system closure. An arbitrary mesh interface (AMI) technique is applied at the sliding interface boundary, which is a circular surface separating between the rotating zone and the fixed zone where the mesh remains stationary. The numerical results allow predicting the vorticity and pressure distributions over a rotating wind turbine for different tip speed ratios in order to characterize the generated wake. The velocity deficit is calculated for different positions behind the rotor to characterize the disturbance rate of the flow.